HUBUNGAN GAYA KEPEMIMPINAN KEPALA RUANGAN TERHADAP KINERJA PERAWAT PELAKSANA DI RUMAH SAKIT X - Royani; Merry Pakpahan (STIKes IMC Bintaro, 2021)
Leadership and Performance are important factors that can be used to increase the success of a hospital in providing the best service in the hospital. The purpose of this study was to determine the relationship between the leadership style of the head of the room and the performance of the nurses at X Hospital, West Jakarta. This cross sectional approach method was carried out on 44 nurses who worked at X Hospital, West Jakarta. Data were analyzed using chi square test. The results of some respondents perceive a democratic leadership style (33; 75%) and have a good performance (22; 50%). There is a relationship between the leadership style of the head of the room and the performance of nurses at X Hospital, West Jakarta (P-Value: 0.045 <0.05). The conclusion of the leadership style of the head of the room on the performance of nurses is expected that an increase in democratic leadership will improve the performance of nurses.